2008
DOI: 10.1111/j.1572-0241.2007.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG Oligosaccharide Alterations Are a Novel Diagnostic Marker for Disease Activity and the Clinical Course of Inflammatory Bowel Disease

Abstract: G0F/G2F is a potentially effective diagnostic marker of disease activity in both CD and UC, and of the clinical course in UC. A pathophysiologic difference between CD and UC was also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Most of them end with either two N-acetylglucosamines (i.e., agalactosylated G0 glycoform), one galactose and one N-acetylglucosamine (G1), or two galactose residues (G2), but a significant, although minor, fraction of galactosylated glycans bears one or two terminal sialic acids (S1 or S2). It has been shown that the proportion of IgG lacking galactose is significantly increased in patients with a variety of chronic inflammatory diseases, most notably rheumatoid arthritis (4,(6)(7)(8)(9)(10). Increased levels of agalactosylated IgG have been shown to correlate with disease severity and also have prognostic value.…”
mentioning
confidence: 99%
“…Most of them end with either two N-acetylglucosamines (i.e., agalactosylated G0 glycoform), one galactose and one N-acetylglucosamine (G1), or two galactose residues (G2), but a significant, although minor, fraction of galactosylated glycans bears one or two terminal sialic acids (S1 or S2). It has been shown that the proportion of IgG lacking galactose is significantly increased in patients with a variety of chronic inflammatory diseases, most notably rheumatoid arthritis (4,(6)(7)(8)(9)(10). Increased levels of agalactosylated IgG have been shown to correlate with disease severity and also have prognostic value.…”
mentioning
confidence: 99%
“…Shinzaki et al 8,10 have demonstrated higher serum agalactosyl IgG in Japanese patients with IBD, and an association with disease prognosis and response to therapy in this population. Another Japanese group reported that glycosylation alterations on IgA antibodies in patients with CD also correlated with disease activity.…”
Section: Discussionmentioning
confidence: 89%
“…5,7 In Japanese patients with inflammatory bowel disease (IBD), the agalactosyl fraction of IgG oligosaccharides was reported to correlate with disease activity and clinical course. 8 Recent data from this group also suggested an association with response to anti-TNF therapy, but the rheumatology literature has not confirmed these findings. 9,10 …”
mentioning
confidence: 94%
“…In 2008, Shinzaki et al [69] reported the diagnostic value of N-linked oligosaccharides of IgG structure (agalactosyl fraction of the fucosylated IgG oligosaccharides [G0F/G2F]) in IBD. Later, the same team reported oligosaccharide alterations of IgA as a novel IBD biomarker in a cohort of 32 CD patients, 30 UC patients, and 30 healthy controls [70].…”
Section: N-acetylgalactosamines Per Hinge Glycopeptidementioning
confidence: 99%